Symposium 2: Virtual networks and the new definition of Knowledge: Towards a policy analysis - Burkle, Martha; Duart, Josep M. (Proceedings of the International Conference on Networked Learning, 2018)
The radical transformation of knowledge access and knowledge production for teaching and learning that higher education institutions around the world are currently experimenting due to the use of technologies and virtual networks, constitutes a platform from which to build new networked learning and new academic interactions. The possibility of instant access to multiple resources of information is transforming the way users around the world access, produce and learn knowledge. However, this significant transformation has not always been echoed by a formal policy agenda at the institutional level. There is still a big gap between technology applications in higher education, and the creation and application of policy strategies to enhance and to regulate these interactions. This paper explores the impact of the Internet in teaching and learning processes at the start of the 21st century and examines the opportunities to stimulate discussion towards policy creation. A discussion about Internet access and differences between Universities in Europe and Africa is introduced. The authors examine the connectivity between users, contents and technologies, and provide a platform for reflection from which to examine the role of the Internet and the creation of virtual environments as important participants of this transformation. Complex processes of knowledge access and knowledge transformation are explored in the framework of policy analysis within higher education institutions around the world.